Energy savings of tissue machines - Flexible application of technologies in different locations - Wen, Zhe (Chalmers tekniska högskola / Institutionen för energi och miljö, 2012)
Nowadays tissue makers are facing many energy related challenges – the increasing energy price, the regulations from government about limitation of energy consumption and various demands from customers in different locations of the world concerning how to increase the energy efficiency and improve their working environment. As one of the leading tissue machine manufacturers, Metso Paper is making great efforts to reduce the energy consumption and increase the energy efficiency of tissue machines. New technologies are developed to reduce the energy consumption and the heat exchanger network is studied to find more valuable heat. To know how to combine the new technologies developed in Metso Paper, a model is developed so that the energy and economic evaluation could be carried out for three different configurations (STD, BAT and BDG) in different locations. Heat recovery is carried out for the drying section of a standard DCT 200 tissue machine in Luleå (Sweden) and Lagos (Nigeria) where district heating and district cooling are in demand respectively. Pinch technology which is a systematic tool for heat analysis is used for process integration. Finally different heat exchanger networks are suggested in these two locations. It is found from the simulation results of the model that the new-developed technologies could bring significant energy savings. The interactions between different components of tissue machines are studied so it is now clear that the electricity production from the turbine will be influenced by the choice of the headbox etc. From the economic evaluation, it is found that the BAT configuration is more profitable for Sweden while BDG is more suitable for Russia. By studying heat recovery in the drying section, it is discovered that the hot moist air from the turbo blower should be considered as a hot stream if it is available. Adsorption chillers should be used in Lagos to transfer the excess heat into the cooling water. With the low gas price in Lagos, the steam generator could be removed so ...